THE DEVELOPMENT OF BLENDED LEARNING-BASED DIGITAL TEACHING MATERIALS ON KINEMATICS FOR ISLAMIC PRIMARY SCHOOL PROSPECTIVE TEACHERS - Amelia, Rizki; Wibowo, Agus Mukti (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
Kinematics is one of fundamental materials in Basic Science Courses for Islamic Primary Schools Prospective Teacher. Kinematics often difficult for student because it needs schematic drawings and formula for motion. Thus, the kinematics teaching materials absolutely needed for Islamic Primary Schools Prospective Teacher. The current findings suggest that the environment in which Islamic Primary Schools Prospective Teachers learn has not been conducive to their growth and development. These initial observations indicate that certain factors may be hindering their progress. Therefore, digital teaching materials are needed that can facilitate the entire science learning process. The purpose of this research is to explicate the development process, along with the validation and comprehensibility of digital science teaching materials as learning media for prospective elementary school teachers in Islamic education. The Lee and Owens development model was used in the creation of this digital teaching material. The Lee Owens developmental model consist of assessment/analysis, need assessment, front-end analysis, design, development, implementation, and evaluation. A material validation questionnaire, media, and a student readability test were used in the questionnaire with Likert scale. The subject of this research are 24 students of Islamic Primary Schools Prospective Teacher in UIN Maulana Malik Ibrahim Malang. The material aspect of product validation showed an average result of 92.08%, while the media validation aspect scored 90.90%. The readability test for digital science teaching materials obtained a score of 83.2%. These findings suggest that digital science teaching materials are highly valid and suitable for use as learning media for prospective Islamic elementary school teachers. As a result, it is possible to conclude that digital science teaching materials are extremely valid and appropriate for use as learning media for prospective Islamic elementary school teachers.